Survey tra fiumi, pianure e colline : l'evoluzione del paesaggio archeologico nel territorio di Santa Croce di Magliano - Marino, Pasquale (Access archaeology., 2021)
This study analyses the territory of Santa Croce di Magliano in the province of Campobasso, Molise, Italy and studies all its archaeological aspects in order to understand patterns of occupation of the human groups that have inhabited it and how they, through the evolution of social interactions, have received extraterritorial influences.